Odpowiedzi

2009-11-17T23:27:14+01:00
Oblicz
1 +3 + 9 +27 +... + 729
a1 =1
q =3
an =a1*q^(n-1)
an =3 ^(n-1)
729 = 3^6 =3^(n-1)
n-1 = 6
n = 6+1 = 7
S7 = a1*[1 -q^7]/(1 -q) = [1 - 3^7]/(1 -3) = [1 - 2187]/(-) =
= -2186/(-2) = 1093
z.2
Ciąg arytmetyczny
a2 =36,
a5 =4,5
a2 =a1 +r
a5 =a1 + 4r
a5 - a2 = (a1 +4r)-(a1+r) = 3r = 4,5 - 36 = -31,5
3r = -31,5
r = -31,5 : 3 = -10,5
a2 = a1 +r
a1 =a2 -r = 36 -(-10,5) = 36 +10,5 =46,5
a10 = a1 +9r = 46,5 +9*(-10,5) = 46,5 - 94,5 = -48
S10 =[a1 +a10]*10 *0,5 = [46,5 - 48]*5 = -1,5*5 = -7,5
S10 = -7,5
1 5 1